Identification and Evaluation of Influential Factors on New Product Commercialization in the Commercial Explosives Industry Based on the Integrated Delphi-Fuzzy and BWM Decision-Making Approach - Saadatzadeh, Reza; Dehghani Poodeh, Hossein; Hajizade , Peyman (Management Strategies and Engineering Sciences, 2024)
Currently, commercialization is one of the most critical elements for the success of new businesses. In our country, due to the presence of human resources that are both innovative and creative, good ideas are often proposed at both the academic and industrial levels; however, unfortunately, they frequently stall at the early stages and fail to move into the production phase. Moreover, due to the existing sanctions in various industries against Iran, areas such as chemicals, mining, and construction such as dam building, road construction, and tunnel construction heavily rely on the development services of the commercial explosives industry. In this study, using both library research and field studies, 24 influential factors in the commercialization of new products in the commercial explosives industry were identified and content-validated in the first step. Subsequently, based on the fuzzy Delphi method, these identified factors were evaluated and screened, with 16 factors confirmed. Then, using the BWM decision-making method, these factors were weighted and ranked. The results of this research can significantly influence the production of new products in the commercial explosives industry by identifying the most important factors affecting new product commercialization. Given the rapid competitiveness in the market, the emergence of new technologies, increasing domestic demand, and the self-sufficiency goal of the country, this study can contribute to more efficient and increased production in this sector.